Metastatic follicular thyroid carcinoma to the mandible - Ajay Prakash Pasupula; Shyam Prasad Reddy Dorankula; Madhusudan Rao Thokala; M Praveen Kumar (Wolters Kluwer Medknow Publications, 2012)
Metastatic tumors are of great significance since few cases may represent the only symptom of an undiscovered underlying malignancy. Metastatic tumors rarely metastasize to the oral region despite the fact that many common primary neoplasms frequently metastasize to bone. The true incidence of metastatic tumors in the bones of the jaw is unknown, as jaws are not always included in radiographic skeletal surveys for metastasis. Sometimes oral metastasis may be the first evidence of metastasis from its primary site. A case of metastatic follicular thyroid carcinoma to the mandible is presented here, along with the discussion of clinical and histological features. The present case not only emphasizes the importance of considering metastasis in the differential diagnosis of a radiolucent lesion in the mandible, but also emphasizes in the improvement of the overall survival rate and treatment results by an early detection of metastatic disease.